Dry reforming of methane: Influence of process parameters-A review - Usman, Muhammad; Daud, Wan Mohd Ashri Wan; Abbas, Hazzim F. (Elsevier, 2015)
This review will explore the influences of the active metal, support, promoter, preparation methods, calcination temperature, reducing environment, particle size and reactor choice on catalytic activity and carbon deposition for the dry reforming of methane. Bimetallic (Ni-Pt, Ni-Rh, Ni-Ce, Ni-Mo, Ni-Co) and monometallic (Ni) catalysts are preferred for dry reforming compared to noble metals (Rh, Ru and Pt) due to their low-cost Investigation of support materials indicated that ceria zirconia mixtures, ZrO2 with alkali metals (Mg2+, Ca2+, Y2+) addition, MgO, SBA-15, ZSM-5, CeO2, BaTiO3 and Ca0.8Sr0.2TiO3 showed improved catalytic activities and decreased carbon deposition. The modifying effects of cerium (Ce), magnesium (Mg) and yttrium (Y) were significant for dry reforming of methane. MgO, CeO2 and La2O3 promoters for metal catalysts supported on mesoporous materials had the highest catalyst stability among all the other promoters. Preparation methods played an important role in the synthesis of smaller particle size and higher dispersion of active metals. Calcination temperature and treatment duration imparted significant changes to the morphology of catalysts as evident by XRD, TPR and XPS. Catalyst reduction in different environments (H-2, He, H-2/He, O-2/He, H-2-N-2 and CH4/O-2) indicated that probably the mixture of reducing agents will lead to enhanced catalytic activities. Smaller particle size (<15 nm) had a significant influence on the suppression of carbon deposition and catalytic activity. Fluidized bed reactor exhibited the highest activity and stability, lower carbon deposition and higher conversion compared to a fixed-bed reactor. Moreover, membrane reactor, solar reactor, high-pressure reactor and microreactor were also investigated with specific features such as: pure H-2 production, detailed reaction information with enhanced safety, higher pressure applications and dry reforming reaction with/without catalyst under sunlight The study of parameters would improve the understanding of various preparation and reaction conditions leading to various catalytic activities. (C) 2015 Elsevier Ltd. All rights reserved.